2017
DOI: 10.1039/c6cp07351d
|View full text |Cite
|
Sign up to set email alerts
|

Achieving enhanced ionic mobility in nanoporous silica by controlled surface interactions

Abstract: We report a strategy to enhance the ionic mobility in an emerging class of gels, based on robust nanoporous silica micro-particles, by chemical functionalization of the silica surface. Two very different ionic liquids are used to fill the nano-pores of silica at varying pore filling factors, namely one aprotic imidazolium based (1-methyl-3-hexylimidazolium bis(trifluoromethanesulfonyl)imide, CCImTFSI), and one protic ammonium based (diethylmethylammonium methanesulfonate, DEMAOMs) ionic liquid. Both these ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 44 publications
14
56
1
Order By: Relevance
“…An increase in conductivity for the lowest studied concentration of salt addition in gel state can be clearly seen in Figure 2, which shows the conductivity vs. molality curves for different temperatures. This behavior agrees with Garaga et al [4], who found an enhancement of ionic mobility after gelation using silica micro-particles, although to our knowledge, studies about the behavior of conductivity with salt addition in gel form have not been previously performed.…”
Section: Electrical Conductivitysupporting
confidence: 93%
See 1 more Smart Citation
“…An increase in conductivity for the lowest studied concentration of salt addition in gel state can be clearly seen in Figure 2, which shows the conductivity vs. molality curves for different temperatures. This behavior agrees with Garaga et al [4], who found an enhancement of ionic mobility after gelation using silica micro-particles, although to our knowledge, studies about the behavior of conductivity with salt addition in gel form have not been previously performed.…”
Section: Electrical Conductivitysupporting
confidence: 93%
“…A main procedure for the sol-gel route in order to prepare gel samples was carried out, using an adaptation of the method described by Garaga et al [4]. A brief description of the selected method is the following:…”
Section: Gelation Routesmentioning
confidence: 99%
“…17 In addition, [DEMA][OMs] was employed to fill nano-pores of silica to enhance the ionic mobility. 19 (3) Studies of the σdc and proton conduction mechanisms. 19−21 Martinelli et al found that the σdc of bulk [DEMA][OMs] obeys a VFT dependence, and that the charge transport mechanism is strongly associated with the vehicle mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…19−21 Martinelli et al found that the σdc of bulk [DEMA][OMs] obeys a VFT dependence, and that the charge transport mechanism is strongly associated with the vehicle mechanism. 19 Yarger et al measured the ionicity and transport properties of a series of diethylmethylamine based PILs by nuclear magnetic resonance (NMR) spectroscopy, and concluded that the gas phase proton affinity is a better predictor of ionicity than the commonly used aqueous ∆pKa. 20 18 ) as received without further purification while other reports also indicated significant water content (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, in immobilizing an IL for gas-solid applications, a relatively weak physical interaction between support and the IL may be adequate owing the very low volatility of the IL [43]. A number of ionogels have been prepared using silica and physical immobilization [39,42,44,45], and their features such as ionic transport and viscoelastic properties have been studied [46,47]. Ionogels incorporating highly hygroscopic ILs can be potentially used as adsorbents for AD but there have been few studies on the hydrothermal stability and adsorption behavior of ionogels.…”
Section: Introductionmentioning
confidence: 99%